Occupational health in the educational context: a descriptive and correlational study - Rodríguez-Fragoso, Javier; José Moya-Faz, Francisco; Horyza, Agata; Ruiz-Ruano García, Ana María; Garcés de los Fayos-Ruiz, Enrique Javier; López-López, Reyes; López Puga, Jorge; Vidal-Alves, María Joao (Frontiers in Education, 2025)
The school context represents a significant occupational risk factor for education professionals. Numerous studies highlight that these professionals often show anxiety, depression, stress or burnout, among other health-related issues. Although various sociodemographic variables have been examined for their influence on the development of these symptoms, there is no clear consensus, especially regarding the role of sex, age or type of teaching. The aim of the present study is to assess psychological well-being and personality traits in a sample of education professionals. The sample includes 257 professionals from public and private centers (Mage = 42.48, SDage = 9.8; 72.4% women). The results show significantly higher scores in women in depression, anxiety, stress and psychological burnout. In addition, professionals under 30 years of age showed greater enthusiasm for their work, but also higher stress levels. Regarding the type of teaching, Primary Education professionals showed higher scores related to burnout, while Early Childhood Education professionals reported a significantly higher stress level. Differences in personality were only observed according to the type of teaching, with significantly higher pleasantness scores in the group composed of management and other professionals. These results underscore the vulnerability of education professionals and highlight the need for more extensive research into their occupational health. Evidence-based interventions targeting this population are also essential to address these challenges effectively.